2019
DOI: 10.1111/hsc.12809
|View full text |Cite
|
Sign up to set email alerts
|

Development and psychometric evaluation of the community care competency scale in multi‐ethnic undergraduate nursing students

Abstract: Preparing healthcare students for community care has been emphasised due to the global ageing population. An instrument to measure students’ community care competency is lacking. This study aimed to develop and evaluate the psychometric properties of a new scale known as Community Care Competency Scale (CCCS) for measuring nursing students’ community care competency. CCCS consists of 21 items derived from literature review and community care standards. Content validity was established through a panel of seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Therefore, the Bartlett's test of sphericity was significant, and the factorability of the correlation matrix can be deduced which means the dataset of the research is suitable for the factor analysis. Lau et al (2019) indicated that Bartlett's test of sphericity was used in assessing a correlation matrix for factor analysis, and it was interpreted that if p < 0.05 as suitable for structure detection.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the Bartlett's test of sphericity was significant, and the factorability of the correlation matrix can be deduced which means the dataset of the research is suitable for the factor analysis. Lau et al (2019) indicated that Bartlett's test of sphericity was used in assessing a correlation matrix for factor analysis, and it was interpreted that if p < 0.05 as suitable for structure detection.…”
Section: Resultsmentioning
confidence: 99%